2012
DOI: 10.1371/journal.pone.0030120
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Transcriptome Profiling of Human Monocytes Exposed Acutely to Cigarette Smoke

Abstract: BackgroundCigarette smoking is responsible for 5 million deaths worldwide each year, and is a major risk factor for cardiovascular and lung diseases. Cigarette smoke contains a complex mixture of over 4000 chemicals containing 1015 free radicals. Studies show smoke is perceived by cells as an inflammatory and xenobiotic stimulus, which activates an immune response. The specific cellular mechanisms driving cigarette smoke-induced inflammation and disease are not fully understood, although the innate immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 65 publications
(92 reference statements)
5
41
0
Order By: Relevance
“…2). and human PBMC with tobacco smoke extract (Wright et al, 2012), and also found glucocorticoid receptor signaling pathway was significant in IPA analysis. Significant down-regulation of glucocorticoid receptor expression was also noted in smoke-exposed mice and in smokers with normal lung function (Marwick et al, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…2). and human PBMC with tobacco smoke extract (Wright et al, 2012), and also found glucocorticoid receptor signaling pathway was significant in IPA analysis. Significant down-regulation of glucocorticoid receptor expression was also noted in smoke-exposed mice and in smokers with normal lung function (Marwick et al, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…Raw fluorescence data files were submitted to GeneSpring GX 13 software (Agilent Technologies) using a widespread and robust method for determining the significant modulation of gene expression (Wright et al 2012;Pisani et al 2015). Eighteen independent analyzes were conducted, namely for each experimental condition (18), three fluorescence data files from exposed cells were compared with three fluorescence data files from unexposed cells.…”
Section: Cell Culture and Analysesmentioning
confidence: 99%
“…15 Microarray analysis RNA was extracted from whole right hearts of mice and converted, and samples were hybridized onto probe sets on an Illumina MouseRef-8v3 BeadChip array, as described elsewhere. 18 Data were analyzed using the syntax package R (ver. 2.3.1) with Bioconductor and limma.…”
Section: Echocardiographymentioning
confidence: 99%